(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Management of Foreign Exchange Rate Exposure by Using Financial Hedging An Analytical Empirical Study The main purpose of this Research is to investigate the ability to reduce the effect of exchange rate fluctuation on firm value , by usage appropriate hedging strategies to provide the firms force to adopted with complex and highly uncertainty conditions , characteristic of the most of the financial markets . The field of this study is the giant five Multinational on the world. Nokia, Toyota Motor, Intel , Coca Cola, Microsoft. practical analysis is provide the truth of all study’s hypothesis , and it is reach to many of conclusion, the most important of them is Stem from unexpected fluctuation on nominal exchange rate , asymmetric transaction exposure. All of, even the Multinational with unique and highly performance, exposes to nominal exchange rate risk .